Defining Reference Values for the Normal Adult Lisfranc Joint Using Weightbearing Computed Tomography - Wijetunga, Chatura Gihan; Roebert, Justin; Hiscock, Richard John; Bedi, Harvinder S.; Roshan-Zamir, Sasha; Wang, Otis; Fraval, Andrew; Tate, Julie; Eden, Maggie; Rotstein, Andrew H. (The Journal of foot and ankle surgery, 2023)
The uninjured contralateral feet of consecutive patients undergoing cone-beam weightbearing computed tomography for acute Lisfranc injury between July 2017 and October 2019 were retrospectively analyzed. Of these, any cases with history or radiological evidence of trauma to the Lisfranc interval were excluded. The area of the non-weightbearing (NWBA) and weightbearing (WBA) Lisfranc joint was calculated (in mm2) using a novel technique. Area difference (AD) was calculated as WBA-NWBA. Area ratio (AR) was calculated as WBA/NWBA. A subset of cases was double-measured by 2 technologists to evaluate inter- and intraobserver variability. A total of 91 patients aged 15 to 74 years were included in the study. The measurement technique was reproducible with excellent intraobserver correlation (intraclass correlation coefficient [ICC]: 0.998, 95% confidence interval [CI]: 0.996-0.999) and high interobserver correlation (ICC: 0.964, CI: 0.939-0.979). The median NWBA was 83 (range 52-171) and median WBA was 86 (range 52-171). Median AD was 1 mm2 (range -3 to 10) and median AR was 1.01 (range 0.96-1.11). No significant difference was identified in AD or AR when adjusted for age, gender, patient-weight or weight put through the foot. Both AD and AR distributions were highly skewed toward 0 and 1, respectively. Based on 95% CI, normal reference range for AD is -1 to 7 mm2 and for AR is 0.98 to 1.09. Absolute area of the Lisfranc joint is highly variable between individuals. The Lisfranc joint is rigid with little to no physiologic widening in most subjects. The normal upper limit of widening of the Lisfranc area on weightbearing was 9%. Differences in age, sex, patient-weight or weight put through the foot were not significantly associated with the extent of joint widening.